2008
DOI: 10.1093/hmg/ddn203
|View full text |Cite
|
Sign up to set email alerts
|

TDRD3, a novel Tudor domain-containing protein, localizes to cytoplasmic stress granules

Abstract: Our previous work has demonstrated that the Tudor domain of the ‘survival of motor neuron’ protein and the Tudor domain-containing protein 3 (TDRD3) are highly similar and that they both have the ability to interact with arginine-methylated polypeptides. TDRD3 has been identified among genes whose overexpression has a strong predictive value for poor prognosis of estrogen receptor-negative breast cancers, although its precise function remains unknown. TDRD3 is a modular protein, and in addition to its Tudor do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 113 publications
(117 reference statements)
6
119
0
1
Order By: Relevance
“…Interaction of SERBP1 with other SG-incorporated RNA-binding proteins SERBP1 has been reported to localize in cytoplasmic SGs that include other proteins such as the ORF1 protein of the LINE-1 retrotransposon [5] and the Tudor domain-containing protein TDRD3 [4]. In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interaction of SERBP1 with other SG-incorporated RNA-binding proteins SERBP1 has been reported to localize in cytoplasmic SGs that include other proteins such as the ORF1 protein of the LINE-1 retrotransposon [5] and the Tudor domain-containing protein TDRD3 [4]. In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2].…”
Section: Resultsmentioning
confidence: 75%
“…SERBP1 interacts with the Tudor domain of TDRD3 and co-localizes to cytoplasmic stress granules (SGs) [4]. The SERBP1 protein was also reported to localize in SGs with the ORF1 protein of the LINE-1 retrotransposon [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, components of germ granules, such as Piwi-family argonautes, harbor methylated arginines that help recruit tudor domain-containing proteins. Interfering with this interaction can impair both localization of tudor-domain proteins, and the methylated proteins themselves, 48,49 as well as germ granule assembly. 50 Such interactions also underpin recruitment of tudor-domain proteins to stress granules.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…This analysis led to the identification of EBMs in the human proteins RRP12 (Oeffinger et al 2004) and TDRD3 (Tudor domain-containing protein 3) (Goulet et al 2008;Linder et al 2008), the uncharacterized protein C2orf68, and the paralog proteins R3HCC1 (R3H and coiled-coilcontaining protein 1) and GIDRP88 (growth inhibition and differentiation-related protein 88) (Fig. 3C).…”
Section: Ebm Motifs Are Present In Additional Proteinsmentioning
confidence: 99%